Analisis Partisipasi Penyusunan Anggaran terhadap Kinerja Manajerial: Komitmen Organisasi sebagai Moderator - Susanti, Vivi Ani (Jurnal Widya Manajemen & Akuntansi, 2004)
This research aims to know the influence of budget participation on managerial performance with organizational commitment as a moderating variable for managers of manufacturing industry that has gone public, listed in Jakarta Stock Exchange and having head office in Jawa Timur. The conclusion is organizational commitment could not be a moderator in interaction between budget participation and organizational commitment analysis to managerial performance.